2016
DOI: 10.1038/srep37229
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of AS03 adjuvant on the plasma cell repertoire following pH1N1 influenza vaccination

Abstract: Influenza pandemics require rapid deployment of effective vaccines for control. Adjuvants such as AS03 improve vaccine immunogenicity, but this mechanism is poorly understood. We used high-throughput B cell receptor sequencing of plasma cells produced following AS03-adjuvanted and non-adjuvanted 2009 pandemic H1N1 vaccination, as well as pre-pandemic seasonal influenza vaccination to elucidate the effect of the adjuvant on the humoral immune response. By analyzing mutation levels, it was possible to distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 40 publications
(84 reference statements)
2
42
0
1
Order By: Relevance
“…Previous studies in humans using AS03-adjuvanted H1N1pdm09 vaccine combined with B-cell receptor (BCR) sequencing of isolated of plasma blasts on day 7 provided evidence for improved recruitment of total antibody secreting cells, that included naïve (unmutated BCR) B cells and recalled preexisting memory B cells in the adjuvanted group compared to the unadjuvanted group. 60 In a separate study, subjects receiving AS03-adjuvanted H1N1pdm09 46 showed an increase in both anti-head and anti-stem antibodies. A significant increase in HI titers against the homologous strain was found in both previously vaccinated (with a seasonal influenza vaccine) or unvaccinated individuals (average fold increase of 32 and 250, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in humans using AS03-adjuvanted H1N1pdm09 vaccine combined with B-cell receptor (BCR) sequencing of isolated of plasma blasts on day 7 provided evidence for improved recruitment of total antibody secreting cells, that included naïve (unmutated BCR) B cells and recalled preexisting memory B cells in the adjuvanted group compared to the unadjuvanted group. 60 In a separate study, subjects receiving AS03-adjuvanted H1N1pdm09 46 showed an increase in both anti-head and anti-stem antibodies. A significant increase in HI titers against the homologous strain was found in both previously vaccinated (with a seasonal influenza vaccine) or unvaccinated individuals (average fold increase of 32 and 250, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Bystander help from T cells can not only lead to higher antibody titers and antibody avidities, but it is also needed for efficient isotype class switching. This is indeed observed for oil in water adjuvants that were tested with IIV in humans [40]. Antibody isotype class switching can be crucial for (universal) influenza vaccine types that rely on antibodies that require Fc receptor mediated mechanisms in order to provide protection, since different antibody subtypes can engage different Fc receptors on effector cells with different efficiencies [1921].…”
Section: Manuscriptmentioning
confidence: 97%
“…Numerous analyses have focused on the frequencies of V(D)J gene usages, which can offer insights into creating biased therapeutic Ab libraries (14)(15)(16). Another therapeutic application of Ab repertoire analysis is advancing vaccine design by comparative longitudinal studies of pre-and postantigen challenge experiments (10,11,(17)(18)(19)(20)(21)(22). Such comparative studies have shown that different individuals can converge on the same Ab sequence against a given vaccine (11,19).…”
mentioning
confidence: 99%